Cigarette Smoke Affects Dendritic Cell Populations, Epithelial Barrier Function, and the Immune Response to Viral Infection With H1N1 - Danov, Olga; Wolff, Martin; Bartel, Sabine; Böhlen, Sebastian; Obernolte, Helena; Wronski, Sabine; Jonigk, Danny; Hammer, Barbara; Kovacevic, Draginja; Reuter, Sebastian; Krauss-Etschmann, Susanne; Sewald, Katherina (Frontiers in Medicine, 2020)
Smokers with apparently “healthy” lungs suffer from more severe and frequent viral respiratory infections, but the mechanisms underlying this observation are still unclear. Epithelial cells and dendritic cells (DC) form the first line of defense against inhaled noxes such as smoke or viruses. We therefore aimed to obtain insight into how cigarette smoke affects DCs and epithelial cells and how this influences the response to viral infection. Female C57BL/6J mice were exposed to cigarette smoke (CS) for 1 h daily for 24 days and then challenged i.n. with the viral mimic and Toll-like receptor 3 (TLR3) ligand poly (I:C) after the last exposure. DC subpopulations were analyzed 24 h later in whole lung homogenates by flow cytometry. Calu-3 cells or human precision-cut lung slices (PCLS) cultured at air-liquid interface were exposed to CS or air and subsequently inoculated with influenza H1N1. At 48 h post infection cytokines were analyzed by multiplex technology. Cytotoxic effects were measured by release of lactate dehydrogenase (LDH) and confocal imaging. In Calu-3 cells the trans-epithelial electrical resistance (TEER) was assessed. Smoke exposure of mice increased numbers of inflammatory and plasmacytoid DCs in lung tissue. Additional poly (I:C) challenge further increased the population of inflammatory DCs and conventional DCs, especially CD11b+ cDCs. Smoke exposure led to a loss of the barrier function in Calu-3 cells, which was further exaggerated by additional influenza H1N1 infection. Influenza H1N1-induced secretion of antiviral cytokines (IFN-α2a, IFN-λ, interferon-γ-induced protein 10 [IP-10]), pro-inflammatory cytokine IL-6, as well as T cell-associated cytokines (e.g., I-TAC) were completely suppressed in both Calu-3 cells and human PCLS after smoke exposure. In summary, cigarette smoke exposure increased the number of inflammatory DCs in the lung and disrupted epithelial barrier functions, both of which was further enhanced by viral stimulation. Additionally, the antiviral immune response to influenza H1N1 was strongly suppressed by smoke. These data suggest that smoke impairs protective innate mechanisms in the lung, which could be responsible for the increased susceptibility to viral infections in “healthy” smokers.